2019
DOI: 10.1021/acsinfecdis.9b00181
|View full text |Cite
|
Sign up to set email alerts
|

MhuD from Mycobacterium tuberculosis: Probing a Dual Role in Heme Storage and Degradation

Abstract: The Mycobacterium tuberculosis (Mtb) heme oxygenase MhuD liberates free iron by degrading heme to the linear tetrapyrrole mycobilin. The MhuD dimer binds up to two hemes within the active site of each monomer. Binding the first solvent-exposed heme allows heme degradation and releases free iron. Binding a second heme renders MhuD inactive, allowing heme storage. Native-mass spectrometry revealed little difference in binding affinity between solvent-exposed and solvent-protected hemes. Hence, diheme-MhuD is for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…When the diheme samples in our study were applied to a Sephadex G-75 column (GE Healthcare), no such separation of oligomeric states was observed. Similarly, analytical ultracentrifugation studies recently showed that diheme MhuD with the His-tag removed by TEV protease exists only as a dimeric protein (19). The aggregation of tagged diheme MhuD would likely impede access of electrons to heme that are required in the catalytic cycle and explain its apparent inactivity as reported previously.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 57%
See 3 more Smart Citations
“…When the diheme samples in our study were applied to a Sephadex G-75 column (GE Healthcare), no such separation of oligomeric states was observed. Similarly, analytical ultracentrifugation studies recently showed that diheme MhuD with the His-tag removed by TEV protease exists only as a dimeric protein (19). The aggregation of tagged diheme MhuD would likely impede access of electrons to heme that are required in the catalytic cycle and explain its apparent inactivity as reported previously.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 57%
“…Reconstituting apo-MhuD protein with heme is also not a trivial endeavor. Since MhuD can bind two hemes in the same active site, special measures must be taken to ensure reliable and consistent heme:protein stoichiometry during reconstitution of monoheme samples to prevent formation of diheme, which was shown to occur even when incubated with heme in a 1:1 molar ratio (19). Therefore, MhuD samples in this study were reconstituted using a CN-CO replacement method that has provided an apparent solution to this challenging problem.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…These K d values are in a range that is similar to what has been reported for other bacterial heme-degrading enzymes. 12,30,31 The binding also appears to saturate at 10 μM, which is a 1:1 HutW:heme ratio. Turnover of HutW Using Metalated and Nonmetalated Porphyrins.…”
Section: ■ Resultsmentioning
confidence: 93%